The Influence of Consumer Dissatisfaction and Competitor Advertising Attractiveness on Brand Switching Through Variety Seeking as an Intervening Variable (Study on Realme Smartphone Users in Surabaya) - Wilda Maulidiyah; Nurhadi Nurhadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
The use of smartphones has grown rapidly on a global scale. However, the increasing popularity and usage of smartphones have led many consumers to exhibit erratic behavior in brand selection. To better understand this phenomenon, this study examines brand switching behavior and its relationship with factors such as consumer dissatisfaction, competitor advertising attractiveness, and variety seeking. This research aims to (1) analyze the influence of consumer dissatisfaction and competitor advertising attractiveness on variety seeking; (2) analyze the influence of consumer dissatisfaction, competitor advertising attractiveness, and variety seeking on brand switching; and (3) analyze the influence of consumer dissatisfaction and competitor advertising attractiveness on brand switching through variety seeking. A quantitative approach was employed in this study. The population consists of Realme smartphone users in Surabaya who have switched to other brands. A total of 140 respondents were selected using purposive sampling based on the Hair formula. Data were collected through questionnaires. The data were analyzed using the Partial Least Squares (PLS) method with the aid of SmartPLS version 4.1 software. The results of the study indicate that consumer dissatisfaction and competitor advertising attractiveness significantly influence variety seeking. Furthermore, consumer dissatisfaction, competitor advertising attractiveness, and variety seeking significantly influence brand switching. Likewise, consumer dissatisfaction and competitor advertising attractiveness, mediated by variety seeking, significantly influence brand switching.